Sistemas de costos por procesos y su incidencia en la rentabilidad de la industria bloquera "Virgen del Cisne", del sector San Felipe, parroquia Eloy Alfaro, cantón Latacunga provincia de Cotopaxi. - Cando Pilatasig, Hugo Patricio (2017)
The present research deals with a comprehensive analysis of the process system costs in the manufacture of blocks and its impact on the profitability of the block industry "Virgen del Cisne", considering that this economic activity is an engine that generates economy for the sector Of San Felipe del Latacunga Canton, Cotopaxi of Province. The elaboration of the block constitutes a continuous and repetitive process that begins from the dosage, mixed, formed and dried; whose stages accumulate significant costs that allow to determine total and unit costs of the block. A process cost system is a tool that is used in those industries, whose production is continuos and in mass, with one or several processes for the transformation of the material until obtaing the final product, allowing to accumulate the elements of the cost for each phase and finally to know the total and unitary cost of the article. Then a cost system will help to identify the investment needed for the production process, avoiding waste of resources and unnecessary efforts that they attribute to the cost of the product. The investigation through the simulation technique allowed to conclude that the production of 52,416 blocks in the month, it is necessary 4,938.5 USD; whose unit cost per block unit is 0.09 USD added a profit of 22%, the P.V.P is 0.11 USD. The application of the profitability indicators allowed to know the real situation of the company, so it is concluded that a system of costs if it affects the profitability of the company.